The optimal method of surgical treatment of patients with floating thrombosis of the iliac-femoral venous segment - O. A. Alukhanyan; R. A. Solovev; Kh. G. Martirosyan; D. S. Aristov; E. A. Petrosyan (Кубанский научный медицинский вестник, 2015)
The scientific work presents analysis of an examination of 78 patients with floating thrombosis in the iliac-femoral venous segment. Аll patients depending on the method of surgical treatment were divided into three groups. First group consists of patients who had had thrombectomy of iliac-femoral venous segment with the plication superficial femoral vein (SFV). Patients from second group has had thrombectomy and ligation of the SFV. Third group consist of patients who had had thrombectomy with resection of the (SFV).In all patients of group I in the remote period the symptoms of chronic venous disease (CVD) were manifested by mild edema and did not exceed grade 3. While in group II at 5% (2) of patients diagnosed grade 4 CVD as trophic disorders of the skin shin, and the terms of recanalization of the thrombosed veins in 38.5% (15) patients have come at a later date in comparison with I group. The worst results were marked in group III. There were more pronounced than in I and II groups the swelling of the limbs and trophic disturbances. Recanalization in the majority of patients of this group 71,4% (10) occurred in the later stages (6-10 months).